Liposomal Delivery of Plant Bioactives Enhances Potency in Food Systems: A Review - Geethi K. Pamunuwa; D. Nedra Karunaratne (Journal of Food Quality)
The potency of plant bioactives may decline drastically upon exposure to harsh external environments including gastrointestinal conditions. The protective role played by liposomes contributes to desirable properties including increased stability, slow/controlled release, improved bioactivity, and enhanced bioavailability of the encapsulated bioactives. Also, the incorporation of plant bioactives encapsulated liposomes in food matrices has resulted in augmented sensory attributes and improved quality of the foods further exhibiting the aptness of liposomal applications in food. Excitingly, new opportunities that circumvent the major shortfalls of utilizing liposomal formulations in the food industry have arisen paving the way to yield food products with high quality.